Detection of somatic copy number deletion of the CDKN2A gene by quantitative multiplex PCR for clinical practice - Tian, Yuan; Zhou, Jing; Qiao, Juanli; Liu, Zhaojun; Gu, Liankun; Zhang, Baozhen; Lu, Youyong; Xing, Rui; Deng, Dajun (Frontiers in Oncology, 2022)
Background A feasible method to detect somatic copy number deletion (SCND) of genes is still absent to date. Methods Interstitial base-resolution deletion/fusion coordinates for CDKN2A were extracted from published articles and our whole genome sequencing (WGS) datasets. The copy number of the CDKN2A gene was measured with a quantitative multiplex PCR assay P16-Light and confirmed with whole genome sequencing (WGS). Results Estimated common deletion regions (CDRs) were observed in many tumor suppressor genes, such as ATM, CDKN2A, FAT1, miR31HG, PTEN, and RB1, in the SNP array-based COSMIC datasets. A 5.1 kb base-resolution CDR could be identified in >90% of cancer samples with CDKN2A deletion by sequencing. The CDKN2A CDR covers exon-2, which is essential for P16INK4A and P14ARF synthesis. Using the true CDKN2A CDR as a PCR target, a quantitative multiplex PCR assay P16-Light was programmed to detect CDKN2A gene copy number. P16-Light was further confirmed with WGS as the gold standard among cancer tissue samples from 139 patients. Conclusion The 5.1 kb CDKN2A CDR was found in >90% of cancers containing CDKN2A deletion. The CDKN2A CDR was used as a potential target for developing the P16-Light assay to detect CDKN2A SCND and amplification for routine clinical practices.